Pendampingan Minat Bakat Bidang Ubudiyyah Santri TPA Roudlotul Muta’allimin - Munir, M (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
This research is conducted based on the interest to know how to actualize interest of talents of the field of the students, the landfill Roudlotul muta'allimin Jati Punggur lengkong Nganjuk, once it is known that the students who are educated in the TPA actually have a lot of potential based on their interests and talents. This research aims to describe the actualization of interest of talents of the field of the students TPA Roudlotul muta'allimin Jatipunggur. This research is a qualitative study using the ABCD (asset based community Development) approach conducted in Jatipunggur Lengkong Nganjuk village. Data collection is conducted at LANDFILL Roudlotul Muta'allimin in the local area by conducting interviews in-depth to informant, observations, documentation studies and recordings. The results of the analysis and interpretation of the research data mention that the potential of the students must be excavated and maximised by referring to the interests and talents they have.